2020
DOI: 10.1088/1361-6463/abc84d
|View full text |Cite
|
Sign up to set email alerts
|

TiO2–SiO2 nanocomposite thin films deposited by direct liquid injection of colloidal solution in an O2/HMDSO low-pressure plasma

Abstract: TiO2 nanoparticles (NPs), 3 nm in size, were injected inside a very-low-pressure O2 plasma reactor using a liquid injector and following an iterative injection sequence.Simultaneously, hexamethyldisiloxane (HMDSO) vapor precursor was added to create a SiO2 matrix and a TiO2-SiO2 nanocomposite (NC) thin film. Both the liquid injection and vapor precursor parameters were established to address the main challenges observed when creating NCs. In contrast to most aerosol-assisted plasma deposition processes, Scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 56 publications
(131 reference statements)
2
40
0
Order By: Relevance
“…Furthermore, it is worthy to note that the production of the matrix, simultaneously with the nanoparticles, reduces the particle-particle interactions, which prohibits their agglomeration. Such characteristic is extensively searched for, especially in the field of deposition of multifunctional nanocomposite thin films [ 47 , 48 ]. Note that the production of nanoalloys using the present process may be used in other processes to obtain devices with specific properties (e.g., catalytic properties).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is worthy to note that the production of the matrix, simultaneously with the nanoparticles, reduces the particle-particle interactions, which prohibits their agglomeration. Such characteristic is extensively searched for, especially in the field of deposition of multifunctional nanocomposite thin films [ 47 , 48 ]. Note that the production of nanoalloys using the present process may be used in other processes to obtain devices with specific properties (e.g., catalytic properties).…”
Section: Discussionmentioning
confidence: 99%
“…Brunet et al [114] attempted to control the coverage percentage through the power supply frequency of the DBD (adjusting the process), whereas Fanelli et al [109] chose to increase the NPs concentration in the solution (by adjusting the precursor). Finally, we [134] showed that it was possible through a specific approach and particularly by optimizing the sequence of injection to tune the TiO 2 NPs content up to 58% while achieving tunable optical properties of the film.…”
Section: Characteristics Of the Produced Nanomaterials Through The Hybrid Approachesmentioning
confidence: 94%
“…As for the most recent reports, our group [134] attempted for the first time the pulsed injection of the colloidal solution (laboratory-made) [135] [136] in much lower-pressure plasma system such as 3 mTorr. The objective of this study was to elaborate TiO 2 -SiO NC thin films though a versatile and agile hybrid process.…”
Section: Low-pressure-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…16) 24) Another effective technique to improve the properties of TiO 2 NPs is to disperse them in a host matrix that has favorable characteristics, such as a large surface area, high light transmittance, and durability, to form a nanocomposite that combines two or more nanomaterials. 25) Among the available matrices, silica (SiO 2 )-based glass and gels (siloxanes and silsesquioxanes) meet all the abovementioned physical and chemical requirements. As a result, SiO 2 TiO 2 nanocomposites have been developed to exhibit superior mechanical, optical, and physicochemical properties to those of TiO 2 NPs.…”
Section: Introductionmentioning
confidence: 99%